Zakat and poverty alleviation in Muslim countries: A Biblioshiny application - Wahyuni, Putri; Wulandari, Ries (Universitas Islam Indonesia, 2024)
IntroductionPoverty is a topic that is hotly discussed in the economic world, especially in developing countries, including Muslim countries. However, research on scientific developments regarding poverty in Muslim countries is still limited.ObjectivesThis study aims to examine trends in the development of zakat and poverty alleviation in Muslim countries using the Scopus database over a period of 32 years from 1991 with the keyword zakat poverty.MethodA bibliometric approach was used to answer this goal by mapping research publications with the help of R-Biblioshiny software.ResultsThe results found 172 document sources discussing this topic, of which 114 journal articles made the largest contribution. The most relevant journal is Journal of Islamic Accounting and Business Research. Apart from that, the largest country's publication contribution is Malaysia, with 160 articles, with the most productive writer Saad Raj, who has a fairly extensive network of author collaborations. Finally, the relationship between words divided into five naming clusters is an important discussion in this research.ImplicationsThe mapping results in this study can serve as a reference for developing new research on zakat and poverty alleviation in Muslim countries in the future.Originality/NoveltyThis study contributes to the mapping of scientific developments on the topic of poverty in Muslim countries.